Hubungan Pengetahuan Ibu Tentang Teknik Meneran Dengan Ruptur Perineum Pada Persalinan - Julia Siahaan; Ernawati Barus; Sidabukke, Ida Ria R (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Childbirth is a series of processes that end with the expulsion of the product of conception by the mother. If the pushing technique is not done correctly, perineal rupture occurs. Perineal rupture is an incident of tearing of the perineal muscles during the labor process. The purpose of this study was to determine the relationship between maternal knowledge about pushing techniques and perineal rupture during labor at the Hamparan Perak Health Center. The design of this study was an analytical survey with a cross-sectional study approach. The research process was carried out in June-August 2024 at the Hamparan Perak Health Center, with a population of 33 mothers giving birth with normal delivery and a sample of total sampling based on inclusion and exclusion criteria with a sample size of 33 respondents. The results showed that the level of knowledge was poor with perineal rupture as many as 21 respondents (63.6%) and good knowledge with perineal rupture as many as 12 respondents (36.4%). The results of the Chi-Square test obtained a p value = 0.001 which means p is smaller than the value of α = 0.05 so that Ha is accepted which means there is a relationship between maternal knowledge about the technique of pushing and perineal rupture during childbirth at the Hamparan Perak Health Center. The conclusion in this study is that there is a relationship between maternal knowledge about the technique of pushing and perineal rupture during childbirth so that it is expected that every health worker, especially midwives, continue to improve their knowledge of the technique of pushing during childbirth.